Upaya Menurunkan Kadar Ion Logam Besi Pada Air Sumur Dengan Memanfaatkan Arang Ampas Tebu - Indah, Dahlia Rosma; Hendrawani, Hendrawani (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The levels of iron metal ions in the well water can cause health problems, causing the yellow color on the walls of the bathroom tub and the yellow spots on the clothes. One way of water treatment is by adsorption technique using charcoal from bagasse. The first step is to first determine the level of iron metal ions in the well water in the village of Palempat, Batulayar District, West Lombok. Furthermore, the well water is contacted with sugar cane bagasse. The manufacture of amphibians includes the sample preparation process, wash with water, drying in the sun, and the refining at 250ÂºC for 2.5 hours then sieved. The sugarcane bagasse that has been put into 100mLsampelair well with a mass of 2 grams of adsorbent. Samples were then stirred at contact time variations of 30, 60, 90, 120 and 150 minutes at 180 rpm using a batch system. The best contact time used to calculate the efficiency of decreasing iron metal ion content is by calculating the difference of iron metal ions before adsorption and after adsorption using charcoal of bagasse. From the research, it was found that iron metal ion content in the sample was 0.1683 ppm. The optimum contact time on iron metal ion adsorption is at 120 minutes contact resulting in optimum adsorption efficiency in iron metal that is 65.83%.